Endemism and long distance dispersal in the waterfleas of Easter Island - Damme, Kay Van (Zootaxa, 2016)
Easter Island is known for a depauperate terrestrial and aquatic biota. The discovery of new taxa is unusual, even among the island’s micro-invertebrates. A new cladoceran, Ovalona pascua sp. nov. (Crustacea: Cladocera: Anomopoda: Chydoridae), is described from freshwater environments. The chydorid, the only known extant cladoceran on the island, is the dominant aquatic invertebrate in the surface waters. Based on detailed morphological comparison, including a character similarity matrix applied across the species in the genus (12 characters/17 spp), the new taxon is proposed here as an insular endemic with affinities in the East (New World). The revision challenges the theory that invasive zooplankton species were introduced from the subantarctic islands during the 18th century. Human introduction is not the main mechanism through which cladocerans could have arrived on Easter Island. Late Pleistocene – Early Holocene fossils in Cañellas-Boltà et al. (2012) from cores in Rano Raraku Lake are identified here as Daphnia O.F. Müller, 1785 (subgenus Ctenodaphnia Dybowski & Grochowski, 1895). The establishment of Daphnia before human colonization on Easter Island provides strong proof of successful long distance dispersal by ephippia over thousands of kilometers of open sea.